2022
DOI: 10.3390/en16010211
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental and Numerical Study on Charged 21700 Lithium-Ion Battery Cells under Dynamic and High Mechanical Loads

Abstract: The need for higher capacity battery cells has increased significantly during the past years. Therefore, the subject of this study is to investigate the behavior of high performance 21700 Lithium-Ion cylindric battery cells under several abuse conditions, represented by high mechanical loads with different velocities and states of charge (SoC), and to develop a finite element analysis (FEA) model, using the OpenRadioss’ explicit solver capabilities. The present study is focused on the investigation of the beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Meanwhile, PCM addition has almost no effect in terms of elongation. A dedicated battery protection system or a reinforced composite, such as carbon fiber, could address this shortcoming of EV battery pack application [50][51][52]. Figure 3 illustrates the substantial rise in the specimen's maximum force and stress when a carbon-fiber-reinforced PCM composite is created using the vacuum infusion process.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, PCM addition has almost no effect in terms of elongation. A dedicated battery protection system or a reinforced composite, such as carbon fiber, could address this shortcoming of EV battery pack application [50][51][52]. Figure 3 illustrates the substantial rise in the specimen's maximum force and stress when a carbon-fiber-reinforced PCM composite is created using the vacuum infusion process.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it should be considered that the cells' FE models are validated under quasistatic mechanical loads. Current studies observed differences in the mechanical behaviour of Li-ion cells between quasistatic and dynamic loads, as the ones that cells are subjected to in the case of a crash [55,56]. These differences in mechanical behaviour can lead to different ISCRs of the metamodels.…”
Section: Limitationsmentioning
confidence: 99%